(untitled) (Global Journal of Medical Research, 2016)
Design, setting, participants & measurements: One hundred and eight patients presented to the University College Hospital Galway, Ireland (UCHG) with upper gastro-intestinal symptoms were included in the study. There were 52 males with age range 18-82 years, mean age 49 years, and 56 females, age range 20-83 years, mean age 52 years. They were grouped according to the endoscopic findings into 4 groups (i) Duodenal Ulcer (DU), (ii) Gastric Ulcer (GU), (iii) Gastritis (GS), & (iv) Non-Ulcer Dyspepsia (NUD). Five milliliter of venous blood was taken in a sterile plain tube; the serum was separated and stored at -70 C0 for ELISA assay. Endoscopy was carried out and at least 4 biopsies were obtained, 2 from the antrum and 2 from the first part of the duodenum (duodenal bulb). One biopsy each from the antrum and duodenum was transferred immediately into a sterile container containing 2 mL of RPMI 1640. The other biopsy specimens one from the antrum and one from the duodenum were processed for histological examination. The serum IgG antibodies to H. pylori and local IgA and IgG were measured by an ELISA test.